2020
DOI: 10.1088/1757-899x/946/1/012004
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of the category of “complex” in terms of dialectical positivism

Abstract: The interpretation of the category of complex is given on the basis of dialectical positivism, in the framework of which the principle of dialectic symmetry is formulated. It, in turn, is based on the consideration of matter and information as paired dialectic categories. In accordance with this principle, information objects form a hierarchy similar to that which corresponds to different levels of matter organization (mechanical, chemical, biological, social). As “complex”, one should interpret the system tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…based on (32), each element of 𝐴 can be associated with a matrix defined by the next formula as (33).…”
Section: Resultsmentioning
confidence: 99%
“…based on (32), each element of 𝐴 can be associated with a matrix defined by the next formula as (33).…”
Section: Resultsmentioning
confidence: 99%
“…A corresponding example was presented in [29], where it was shown that there are conditions under which any voting council is converted into a kind of analogue of a neural network. This example is informative because it allows one to prove that under certain conditions, a decision on a particular issue is made not by a set of Council members, but by a neural network formed from them, which itself has a certain distributed memory.…”
Section: Discussionmentioning
confidence: 99%
“…Direct calculation shows that the spectrum in Figure 7 is the product of the spectra in Figure 6 and 3. The resulting formula (25) makes it possible to use a direct analogue of the transfer function for digital periodic signals. Such an analogue is the set of quantities (⃗⃗ , ), appearing in (25).…”
Section: Description Of Linear Systems In Terms Of Generalized Rademacher Functionsmentioning
confidence: 99%
“…The resulting formula (25) makes it possible to use a direct analogue of the transfer function for digital periodic signals. Such an analogue is the set of quantities (⃗⃗ , ), appearing in (25). As in classical radio engineering, the description of any linear operation that has the property of invariance with respect to a shift in time is reduced to an indication of its transfer function.…”
Section: Description Of Linear Systems In Terms Of Generalized Rademacher Functionsmentioning
confidence: 99%